Drinking water calibration and suitability in Omdurman: A case study of the North and Southwest Omdurman areas (The International Journal of Educational Sciences and Arts, 2026)
This study addressed the importance of Water as a vital resource for human survival in terms of both quantity and quality as well as the associated geographic factors that create problems hindering its safe use and the resulting social and economic impacts. The research problem focuses on answering: To what extent is water suitable for various human uses, and who well does it comply with regional and international standards? It also seeks to identify the most significant geographical factors affecting changes in the chemical properties of water, and challenges facing its safe utilization.The significance of the study lies in intrinsic importance of the topic, as it represents a relatively new area in terms of content within the study region, in addition to its academic value by providing a scientific study that addresses drinking water issues, benefiting relevant authorities ang decision-makers.The objectives of study include reviewing the most important regional and international standards for water suitability, examining the current status of drinking water and supply identifying key health problems associated with water, and determining the role of responsible institutions in addressing these issues. The study methodology involved the use of the descriptive-analytical method and statistical techniques for data collection, classification. And analysis to reach realistic conclusions. The study reached several findings, the most important of which are the existence of problems related to changes in the physical, chemical and biological properties of water. It also emphasized the importance of water management and monitoring its distribution within the local area particularly in residential areas.The key recommendation include improving environmental health, raising health ,raising health and environmental awareness regarding water, emphasizing the importance of water sources and resources and activating studies and research in the field of drinking water treatment  and purification using modern technological methods >
Keywords: Water sources; Water problems; Omdurman Locality